Nuove Prospettive Tecnologiche e di Servizio per l'Aerospazio - Nicolai, Giovanni (GEOmedia, 2018)
Advances in technology have split the space community to focus on the miniaturization of conventional satellites, making smaller satellites increasingly popular every day and in recent years several small satellites have been launched (nano, micro and mini)